STRUCTURE OF THE INTERNATIONAL FUND FOR SAVING THE ARAL SEA AND ITS HISTORICAL SIGNIFICANCE IN STABILIZING THE ECOLOGICAL SITUATION IN THE REGION - Hikmatjon Kenjayevich Avezov (Modern American Journals, 2025)
This article provides a scholarly analysis of the establishment, structure, operational directions, and role of the International Fund for Saving the Aral Sea (IFAS) in ensuring ecological sustainability in the Central Asian region. The study is conducted following the IMRAD (Introduction, Methods, Results, and Discussion, Conclusion) framework and is based on historical processes, statistical indicators, and reports of international organizations. The Introduction and Methodology sections cover the root causes of the regional ecological crisis and the scientific approaches employed in its study.
Keywords: Aral Sea, IFAS, ecological sustainability, ASBP, transboundary water resources, international cooperation.